(untitled) (SCIENCE TIME JOURNAL, 2026)
This article discusses the main types of corpus-based activities used in vocabulary teaching in foreign language education. It highlights the role of language corpora in improving learners’ lexical competence through authentic language examples and contextual analysis. The study focuses on activities such as concordance analysis, collocation tasks, frequency-based exercises, contextual guessing, and data-driven learning. The article emphasizes that corpus-based activities increase learner autonomy, critical thinking, and practical vocabulary usage in communicative contexts.